The Effect of Experiential Marketing and Brand Image on Customer Satisfaction - Syafira Dzikria Alfiani; Indira Rachmawati (Almana : Jurnal Manajemen dan Bisnis, 2020)
Consumer satisfaction is important for a company. In an effort to meet customer satisfaction, many efforts can be done such as providing an unforgettable experience for consumers and creating a good brand image in the eyes of consumers. Garuda Indonesia is a company that applies the Garuda Indonesia Experience concept, which is a concept that is applied to provide a unique experience in an effort to gain customer satisfaction. This research method uses quantitative methods with purposive sampling and takes a total of 400 samples obtained through Google Form. The data analysis technique used is Structural Equation Modeling with LISREL. Based on the results of this study, the results show that experiential marketing has a positive and significant effect on customer satisfaction, brand image has a positive and significant effect on customer satisfaction, and experiential marketing and brand image have an effect on simultaneously customer satisfaction of Garuda Indonesia airlines.